Integrated multi-domain system modelling and simulation for offshore crane operations. Issue 1 (February 2015) - Chu, Y.; Æsøy, V.; Ehlers, S.; Zhang, H.
Abstract : Advanced offshore machinery, such as an offshore crane, usually involves several energy domains. Modelling and simulation of multi-domain systems is challenging because of not only the complexity in modelling of the related sub-systems but also the interfacing of these sub-models in an integrated model and the performance of simulating, especially when real-time simulation is required. This paper introduces a modelling approach for offshore crane operations based on the bond graph (BG) method. Specifically, the integrated model includes mechanical properties, hydraulic actuators and control algorithms. For the purpose of testing, particularly of advanced control algorithms, it is necessary and crucial to include the response of physical systems. In this paper, a flexible control algorithm for offshore crane operation, including functions of heave compensation and load anti-sway, was implemented.